Sustainable economic governance: learning from Kautilya's Arthashastra. (2017) - Manrai, Rishi; Goel, Utkarsh
Sustainable economic governance requires effectual rules and policies and their effective implementation. Arthashastra written by Kautilya more than two thousand years ago discusses various best practices on governance of markets, economics and trade to ensure happiness and wellbeing of the subjects. Most of the wisdom of Arthashastra are still relevant and are being adopted knowingly or knowingly by present day governments. This paper discusses the teachings of Arthashastra on critical economic policy areas and their key elements and tries to relate its application with present day scenario. The paper discusses how Arthashastra lessons on public finance, trade, taxation and administration have been or can be incorporated in Indian context to achieve the ultimate objective of sustainable economic governance. The paper further combines the key teachings on economic governance and presents a model which can act as a guide for good economic governance.